Supporting Tools for Early Stages of Architectural Design. (December 2014) - Bueno, Ernesto; Turkienicz, Benamy
In architectural design, pencil and paper remain the most frequently used media to create freehand drawings to support early design stages. Digital tools conventionally used by architects lack appropriate functionalities and do not offer friendly interfaces for the early stages of architectural design. These are the bad news. The good news are twofold: A) hardware already available can help freehand designers to digitally express their first ideas; and b) functionality principles present in experimental software combined with appropriate hardware could successfully provide a friendly and intuitive human-computer interaction in the early stages of architectural design. This paper takes special attention to the way architects interact with computers, how input devices constrain possible interactions and how functionalities can be explored through these interactions. The article summarizes basic principles to be considered in the development of an all-in-one software and create a scenario whereby these principles are simulated on a hypothetical software to be used during the early stages of architectural design.